Ruxolitinib in adult dermatomyositis with anti-TIF1γ antibody: a case report and literature review - Jing, Xu; Min, Wang; Xia, Liu; Shanshan, Li (Frontiers in Immunology, 2025)
Ruxolitinib is a selective JAK1/2 inhibitor, and its application in treating adult-onset dermatomyositis(DM) has rarely been described. Here, we report a case of an adult-onset DM patient with anti-TIF1γ antibody, who also suffered from essential thrombocytosis related to the JAK2 V617F mutation. Her clinical symptoms of DM markedly improved after ruxolitinib treatment, whereas her platelet count did not significantly change. In addition, we reviewed previous studies on the treatment of adult DM with ruxolitinib, and summarized reports of the JAK2 V617F mutation in adult idiopathic inflammatory myopathy.